2020
DOI: 10.1108/lhs-11-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of authentic leadership and patient care quality

Abstract: Purpose The purpose of this study is to investigate the causal relationships between the dimensions of authentic leadership and patient care quality in the nursing profession of Ghana. Design/methodology/approach The study used explanatory and cross-sectional survey designs. The data were obtained from 400 respondents, consisting of 200 nurses and 200 patients in selected general hospitals. The analysis was done using descriptive statistics, correlation and multi-linear regression techniques. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 53 publications
0
42
0
3
Order By: Relevance
“…Moreover, this may affect the quality of patient care quality. It is emphasized that the dimensions of authentic leadership, such as self-awareness, predict patient care quality [ 38 ]. The results of studies in the group of nurses confirmed a relationship between self-efficacy and AL skills [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this may affect the quality of patient care quality. It is emphasized that the dimensions of authentic leadership, such as self-awareness, predict patient care quality [ 38 ]. The results of studies in the group of nurses confirmed a relationship between self-efficacy and AL skills [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence exists in the realm of nursing linking authentic leadership of nurse leaders with enhanced nurses' work outcomes (Kida et al., 2020; Maziero et al., 2020; Regan et al., 2016) and heightened psychological well‐being (Wei et al., 2020; Alilyyani et al., 2018; Shirey et al, 2019). However, there are limited yet valuable reports that relate authentic leadership to patient safety outcomes including fewer adverse events (Asif et al., 2019; Wong et al., 2013) and improved care quality (Puni & Hilton, 2020; Laschinger & Fida, 2015). A systematic literature review by Alilyyani et al.…”
Section: Introductionmentioning
confidence: 99%
“…Authentic Leadership can result in greater motivation to engage in leadership roles as it creates a healthy work environment and promotes leadership self-efficacy (2) . Furthermore, a study suggests that Authentic Leadership is associated with the quality of customer service (3) .…”
Section: Introductionmentioning
confidence: 99%